SPECULATION CONCERNING SPECIATION IN CORAL REEF FISHES - Nursall, J. R. (Marine Research in Indonesia, 1977)
The relatively constant equatorial marine environment provides a milieu within which biotic factors provide the chief selective forces acting on fish species. Increasing diversity increases evolutionary opportunity by heterotrophic magnification. Niche availability is almost limitless, space (volume) is the ultimate constraint. Abiotic thresholds, e.g., seasonal isotherms, are filter barriers to emigration to higher latitudes. Beyond such thresholds, abiotic, factors become the chief selective forces acting on fish species.